Marine Fisheries in Nigeria: A Review (2018)
Fisheries production especially from marine is important for the socio-economic development of Nigerians and its contribution to the nation’s economic growth through the Gross Domestic Product (GDP). Nigeria is blessed with enough marine fisheries resources that could enhance increased fish production. Yet, fish supply from domestic production is far below the fish demand of her citizens. This chapter is therefore focused on marine fisheries in Nigeria. We adopted a desk review approach. This chapter is divided into different sections such as the Nigerian fisheries sector, marine fisheries resources in Nigeria, status of marine fisheries production in Nigeria, marine fisheries regulations, and constraints to optimal marine fisheries production in Nigeria. We concluded that the contribution of aquaculture to marine fisheries production has been low, compared to the marine capture fisheries production. Also, we noted that despite the availability of regulations, noncompliance by fisher folks has not helped to optimize marine fisheries production. We therefore recommended that the culture of marine fishes should be intensified. Marine waters should also be protected against destruction and pollution as a result of human activities. Available marine fisheries regulations should be enforced and violators of the regulations should be punished as stipulated in the regulations.